Effect of nail thickness on visible radiation transmittance: implications for new photodynamic therapy technologies in onychomycosis - Navarrete-de-Gálvez, Enrique; Aguilera-Arjona, José; De-Gálvez-Aranda, María Victoria; Fonda-Pascual, Pablo; Herrera-Ceballos, Enrique; Gago-Calderon, Alfonso (Wiley, 2020)
Photodynamic therapy is taking importance as a nonintrusive treatment for nail onychomycosis. Knowledge of true transmittance values across nails could lead to qualitative and quantitative improvements in light- based treatments. We have characterized the spectral transmittance of healthy and fungally infected human fingernails and toenails according to nail thickness, and we propose a surface transmittance model for the small-scale optimization of light-based treatments. Transmittance of fingernails and toenails was analyzed by means of spectroradiometric measurements under solar-simulated visible light radiation (400 nm to 750 nm). The nail thickness was measured by means of microscope measurement. Transmittance was highest at longer wavelengths and decreased gradually as the wavelengths became shorter but with a significant nail transmittance of around 20% in the blue region of the spectrum. In the case of nails affected by onychomycosis, transmittance fell to under 10% because of the thickness of the nails, with no changes in spectral characteristics of transmitted light. Nail thickness is the main variable controlling exponentially light transmission in the visible spectrum and not only red radiation is effective for nail onychomycosis PDT. Blue light, the spectral band more effective for PPIX absorption is also effectively transmitted.
Keywords: Diodos emisores de luz; Terapia fotodinámica; Onicomicosis; Dispositivos LED; Transmitancia de la radiación visible